Electrical Power Transformer Health Condition Assessment Using Health Index Model - ALASHI, LUBNA (2023)
Power Transformer is the principal to preserve Transmission network operation and is required to ensure the stability of the power grid. Over time, Power Transformer is degrading, and it is essential to assess its condition to avoid system interruptions and breakdowns. Moreover, condition evaluation may help to regularly revise and adjust the maintenance strategy to effectively optimize the recourses used with respect to the desired quality. Health Index formulation is one of the effective models to evaluate the asset condition. It comprises a series of evaluation parameters combined into a single value to indicate the health index from different aspects for the best asset management planning. This study aims to develop a Health Index model for Power Transformers based on the most suitable parameters. Furthermore, the research will propose a decision-making Flow Chart for the maintenance requirements and determining the remaining life. The major parameters selected in this research are electrical and laboratory tests, location, age, and site observations. Basically, the existing methods of Health Index are usually a combination of experts’ knowledge and data-driven. Therefore, the method used in this research is the scoring and weighting method to evaluate the parameters using experts’ experience, international standards, and previous studies. The data is collected based on a real case study of Three Power Transformers in the Middle East region. Further, a Flow Chart diagram is established to make a decision on the most appropriate maintenance requirement needed for each Power Transformer. After that, the remaining expected life is also determined. The findings of the Three Power Transformers states are Good, close to Fair, and close to Poor. Accordingly, further enhancement is required for the two Power Transformers by adjusting the maintenance plan and continuously monitoring their condition. A replacement plan should also be prepared as both Power Transformers' end of life are less than Ten years. In conclusion, the key factor in establishing a successful Health Index model is selecting realistic and suitable parameters, scores and weight.